RELATIONSHIP OF SUGAR, SALT, AND FAT CONSUMPTION TO RATIO OF WAIST TO HIP AND BLOOD GLUCOSE LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS - Zuhria Ismawanti; Nastitie Cinintya Nurzihan; Oktavina Permatasari (Jurnal Gizi Prima (Prime Nutrition Journal), 2022)
Background: Diabetes Mellitus (DM) is a chronic hyperglycemia condition that can affect all body systems. This situation is caused due to factors that inhibit insulin work or the amount decreases. Being overweight is also closely related to daily food intake, significantly contributing calories, such as sugar, salt, and fat. An indicator that can determine central obesity is the waist-to-hip ratio. Research Methods: This type of research is a cross-sectional study with an analytic observational study design. The sampling technique uses purposive sampling, and the total is 161 respondents. This research is in Gambirsari Public Health Center, Surakarta, Indonesia, in April 2020. Data on the Consumption of sugar, salt, and fat respondents used a Semi-Quantitative Food Frequency Questionnaire form and 24-hour food recall. Research Result: Test data analysis using Pearson using SPSS 23 software. Sugar consumption (p = 0.004, r = 0.229), salt (p = 0.001, r = 0.454), fat (p = 0.021, r = 0.181) indicates a relationship to the waist-to-hip ratio. Conclusion: Based on statistical analysis, it was found that there was a significant relationship between sugar, salt, and fat intake and the waist-to-hip ratio